Lelaki berpakaian seperti perempuan: antara gender identity disoder, undang-undang Syariah dan perlembagaan Malaysia / Yuhanza Othman … [et al.] - Othman, Yuhanza (2015)
Syariah law prohibits cross dressing among a Muslim male and those who cross-dress shall be criminalized and convicted. Although we have specific Syariah enactments in each state in Malaysia on express prohibitions for cross dressings, not to mention Quranic verses on this matter, there are still cases of cross dressings in Malaysia. Recently, in Malaysia, the issue of cross dressing was intensely discussed when the Court of Appeal in 2 January, 2014 allowed the appeal made by three Muslims males who claimed they had the right to dress like a woman. The three appellants argued that they were suffering from Gender Identity Disorder (GID) which made any charges against them under Section 66 of the Syariah Criminal (Negeri Sembilan) Enactment 1992 null and void. They also challenged that the charge that was brought against them by Department of Islamic Religious Affairs of Negeri Sembilan was unconstitutional and infringed their rights. Thus, this writing attempts to analyze the judgment given by the judges in favor of the three appellants by discovering the issues of GID. It is hoped that this paper will give a clear picture to the public about cross dressing in Islam and the use of GID as medical evidence in courts with regard to the issues of transgender.